Analysis of Spatiotemporal Evolution Characteristics of Dry and Wet Events in Sichuan Province from 1960 to 2019 - HUANG Yi; LI Yunyun; FAN Jingjing; ZHENG Junwei; ZHANG Qing (Renmin Zhujiang)
Sichuan Province has a large population and experiences substantial regional climate heterogeneity,resulting in differential sensitivity of dryness and wetness to meteorological changes.Examining the spatiotemporal evolution characteristics of dryness and wetness can provide a basis for local departments to take countermeasures against climate change.The dry and wet events in Sichuan from 1960 to 2019 and their intergenerational and seasonal characteristics are identified and described based on run theory.The trend,significance,and periodicity of dry and wet events are described by the Mann-Kendall test and wavelet analysis.The results show that Sichuan Province experienced the highest frequency of dry and wet events in the 1990s and the lowest frequency of the events in the 2000s.Western Sichuan is the driest,while eastern Sichuan is the wettest,with both reaching peak dry and wet event counts in the 1980s.In Sichuan,drought events occur mainly in spring and winter,while humid events occur mainly in summer and autumn.Drought events occur mainly in western Sichuan in spring,and humid events occur mainly in western and northern Sichuan in autumn.The western and northern Sichuan areas tend to be humid,while the southern and eastern Sichuan areas tend to be dry.Except for southern Sichuan,the standardized precipitation evapotranspiration index (SPEI) sequence in summer shows a downward trend in other areas,while the downward trend of the SPEI sequence in winter slows down in western and eastern Sichuan areas.